Generalized evaluation of oil and gas pollution in Mangystau region (Eurasian Journal of Ecology, 2018)
The authors have developed a way to solve the inverse problem of integrated environmental assessment with the help of GIS technologies andmodels of the objective function on the basis of the available in the Atlasof Mangystau region maps with ready-made, integrated environmental assessment, take into account the effect of all sources of exposure. As previously published, oil and gas complex of Mangystau region in anthropogenic modification of the most important components of the environmentare examples of its decision the review stage works are considered to estimate the contribution of activity – relief, soils and vegetation. The resultsof these calculations have shown that the oil and gas complex providesan additional contribution to the degradation of soil cover in excess of theaverage for all anthropogenic sources at the 19.31%, in relief degradation– 18.3%, vegetation – 16.7%. In this article, we consider the estimation ofthe impact of oil and gas complex in the groundwater.In this article, we consider the assessment of the impact of oil and gascomplex in the groundwater. Specificity of this evaluation is the need todetail the existing scale of the expert assessment of the level of anthropogenic disturbance of groundwater levels in three to five, as the necessaryfrom the standpoint of ensuring sufficient accuracy of the environmentalassessment in accordance with the recommendations of the environmentalengineering, and from the standpoint of the possibility of “cross-linking”of all received solutions at integrated complex environmental Assessment.For a detailed map of the grading scale used natural protection of groundwater, published in the Atlas of the Mangystau region. Square contourscombinations of 3 levels of anthropogenic disturbance with 4 levels ofnatural protection of groundwater, and then with hydrocarbons locationareas defined in Arc GIS, the use of which components have greatly simplified the task, as after the procedure each loop sampling were receivedvector shapefiles, areal values are displayed automatically in the derivationof each circuit. The calculated objective functions have shown that theoil and gas complex creates an additional burden on the vegetation, exceeding the average of all anthropogenic sources by 9.9%. A summary ofthe assessment called because in the objective functions include numericexpression sums of squares of each level of anthropogenic disturbance,first across the region, and then for areas with the presence of oil and gascomplexKey words: Mangystau region, oil and gas complex, the degree of anthropogenic disturbance of groundwater, the natural protection of groundwater geographic information system, the objective function.